Bacteriological and Enzymatical Study on Rheumatoid Arthritis Patients - Teeba Fares Hadi (Journal of Global Pharma Technology, 2017)
The current study included the collection of 175 samples(blood-urea)of patients suffering from rheumatism, collected from Baghdad Teaching Hospital (Educational Laboratory), Al- Kindy Teaching Hospital, Al-Imamian Al-Kadhimya in Medical City in Baghdad at different duration between 2016/10/1 -2017/2/1. The bacterial growth results showed that 80% of urea samples positive for bacterial culture, while the rate of samples did not show any bacterial grow this 20%. The isolation subjugates to morphological, microscopically and biochemical tests, as also diagnosis by Api system. The most frequent bacterial pathogenic is E. coli which appeared highly rate(41.97)% followed by E. cloacae (21.25)%,P. aeruginosa (12.5)%, Salmonella (10)% and the proportion of K. pneumonia(7.5)%, while S. marcescens showed (6.25)%. When the measurement of the concentration of liver enzymes Glutamic Oxalate Transaminase (GOT), Glutamic Pyruvate Transaminase (GPT), Alkaline phosphates’ (ALP), the results showed a significant degreaseP≤0.05 in the level of enzyme GPT in patients serum which reachto16.94±0.84 mg/ml, while its level in the healthy serum was 0.68± 6.78 mg / ml.ALP enzyme results showed non-significant high atP≤0.05 in the level of patients serum with rheumatoid arthritis, as it reached the level in the serum 2.46±134.42 mg/ml, while the level in the healthy serum was 0.50±4.11 mg/ml. The enzyme GOT showed on-significant high at P≤0.05 in the level of patients serum as it reached the level in the serum 0.88±21.51 mg/ml, while the level in the healthy serum was 0.50±4.11 mg/ml.Keywords: Liver enzymes, Rheumatoid arthritis, Bacteria.